2015
DOI: 10.1016/j.seizure.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Termination patterns of complex partial seizures: An intracranial EEG study

Abstract: Purpose While seizure onset patterns have been the subject of many reports, there have been few studies of seizure termination. In this study we report the incidence of synchronous and asynchronous termination patterns of partial seizures recorded with intracranial arrays. Methods Data were collected from patients with intractable complex partial seizures undergoing presurgical evaluations with intracranial electrodes. Patients with seizures originating from mesial temporal and neocortical regions were group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Comparing the pre-ictal and the immediate postictal time periods in regard to iEEG characteristics or neuropsychiatric state of the patient (Ito, 2010) clearly reveals that the dynamics leading into a seizure are qualitatively different from those occurring at seizure termination (Afra et al, 2015) and bringing about the post-ictal state. If pre-seizure dynamics were similar to the often slowly fading, post-ictal phenomena, seizure prediction might be much easier to achieve (Mormann et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparing the pre-ictal and the immediate postictal time periods in regard to iEEG characteristics or neuropsychiatric state of the patient (Ito, 2010) clearly reveals that the dynamics leading into a seizure are qualitatively different from those occurring at seizure termination (Afra et al, 2015) and bringing about the post-ictal state. If pre-seizure dynamics were similar to the often slowly fading, post-ictal phenomena, seizure prediction might be much easier to achieve (Mormann et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Unequivocal seizure onset was defined as any epileptiform signal pattern that became clearly identifiable without knowing that a seizure followed. Seizure termination was determined as the time point when epileptiform signals vanished, which often manifested itself as a generalized and sudden decrease of amplitude and frequency (Schindler et al, 2007, Afra et al, 2015.…”
Section: Visual Ieeg Analysismentioning
confidence: 99%
“…It has commonly been assumed that seizures and their immediate clinical manifestations stop simultaneously, after which there is a period of gradual postictal recovery. In reality, seizure activity may continue in some regions after having ceased in others 1 , and the postictal period may contain striking electrographic or clinical features. Postictal EEG analysis has largely focused on regional slowing or attenuation 2 and postictal generalized EEG suppression, or PGES 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent work showed that an increase of the synchronization between the thalamus and the cortex facilitates the end of the seizures [35]. Moreover, 88% of CP seizures in mesial temporal epilepsy had a synchronous pattern of termination [36]. Our hypothesis is that if the disconnection originated by the decrease in DoL, found in the PS, is not able to stop the seizure, there would be a spread of the seizure to other brain areas, causing longer and worse behavioral postictal changes, as seen during CP seizures.…”
Section: Discussionmentioning
confidence: 78%